Eksegetis Yudas 1:20-21: membangun diri dalam iman dan implikasinya terhadap Against Heresies - Imanuel Umbu Zawila Deke (Sekolah Tinggi Teologi Sangkakala Jakarta, 2025)
ABSTRACTThis paper explains the importance of strong faith as a foundation for defending oneself and resisting false teachings. Jude advises believers to build themselves on the foundation of their most holy faith. This study uses a library research method by combining various journal and book sources and a hermeneutic system to discover the meaning of Jude 1:20-21. The results of the study show that Jude 1:20-21 is relevant in the lives of believers today. First, believers must build themselves in a solid faith in Christ as a foundation for opposing and resisting false teachings. Second, believers in building faith must be under the guidance of the Holy Spirit as the nurse of their faith. Third, believers must maintain their faith in God's love and not distance themselves from God's love. The identity of a believer is seen from a strong faith so that it is not influenced by false teachings that threaten the believer's life. Believers must continuously build faith in Christ.Â Keywords: Jude 1:20-23, faith, believer, Againts Heresies.Â ABSTRAKTulisan ini menjelaskan pentingnya iman yang kuat sebagai fondasi dalam mempertahankan diri serta melawan pengajaran sesat. Yudas menasehati orang percaya untuk membangun diri di atas dasar iman yang paling suci. Penelitian ini menggunakan metode penelitian kepustakaan dengan memadukan berbagai sumber jurnal dan buku serta sistem hermeneutik untuk menemukan makna dari Yudas 1:20-21. Hasil penelitian menunjukkan Yudas 1:20-21 relevan dalam kehidupan orang percaya masa kini. Pertama, orang percaya harus membangun diri dalam iman yang kokoh di dalam Kristus sebagai fondasi untuk menentang dan melawan pengajaran sesat. Kedua, orang percaya dalam membangun iman harus di bawah pimpinan Roh Kudus sebagai perawat iman dari orang percaya. Ketiga, orang percaya harus memihara imannya dalam kasih Allah dan tidak menjauhkan diri dari kasih Allah. Identitas orang percaya adalah dilihat dari iman yang kuat sehingga tidak dipengaruhi oleh pengajaran sesat yang mengancam kehidupan orang percaya. Orang percaya harus membangun iman kepada Kristus secara terus-menerus.Â Kata Kunci: Yudas 1:20-23, iman, orang percaya, Against Heresies.